Literatura jako ilustracja zagadnień gramatycznych i leksykalnych – casus górnołużycki - Bura, Renata (Slavia Occidentalis, 2023)
This article raises the issue of using fiction to present grammatical and lexical phenomena. The subject of the study is the most important Upper Sorbian grammars (Hinc Šewc Gramatika hornjoserbskeje rěče, 1968 and 1976; Helmut Faßke, Siegfried Michalk Grammatik der obersorbischen Schriftsprache der Gegenwart. Morphologie, 1981) and a phraseological dictionary (Anatolij Ivčenko, Sonja Wölke Hornjoserbski frazeologiski słownik, 2004). The aim of the study is to assess the usefulness of linguistic material taken from fiction for illustrating grammatical and lexical issues. The material contained in the mentioned grammars and dictionaries also says a lot about the language of the most frequently cited authors.